PARÉSIA FACIAL PERIFÉRICA BILATERAL - Paiva, Sofia; Morgadinho, Ana Sofia; Neves, José Carlos; Amorim, Ana Margarida; Gapo, Carla; Soares, Vera; Costa, Sandra; Romão, José; Sofia, Carvalho; Paiva, António (Revista Portuguesa de Otorrinolaringologia-Cirurgia de Cabeça e Pescoço, 2005)
.